Toward the Association Between EFL/ESL Teachers' Work Engagement and Their Students' Academic Engagement - Zhang, Aizhen; Yang, Yang (Frontiers in Psychology, 2021)
Given the fact that EFL/ESL students’ academic engagement is of high importance for their learning success, numerous studies have been carried out to identify factors contributing to students’ engagement. However, the role of teacher personal factors, notably teacher work engagement has received scant attention. Moreover, no review study has been conducted on this issue. Accordingly, the present review intends to explicate the multidimensional essence of teacher work engagement and student academic engagement and the association between these constructs. In light of the theoretical and empirical evidence, the role of EFL/ESL teachers’ work engagement in improving their students’ academic engagement was proved. The pedagogical implications of the findings are also highlighted.